Injectable Gel Type Formulation of Hydrated Egg Phosphatidylcholine and Hyaluronate for Local Drug Delivery - SangGyunKim; HessonChung; InHyunLee; SeungBackKang; IckChanKwon; HaChinSung; SeoYoungJeong (한국약제학회, 2002)
gel composed of egg phosphatidylcholine (egg PC), hyaluronate (HA) and water was formulated for local drug delivery. The lamellar liquid crystalline structure of the egg PC/water system did not change by adding HA in the formulation. However, egg PC/HA/water gel was more resistant to erosion than the egg PC/water gel. The egg PC/HA/water and egg PC/water gels containing model drugs, tetracycline and sudan IV were prepared to perform in vitro and in vivo drug release experiments. In vitro release of tetracycline was sustained in the gel type formulations. The release rate of hydrophobic sudan IV was extremely slow. More than 99% of sudan IV remained inside the gel after 5 days. In vivo release of drugs from the air pouch model in Balb/c mice shows that lipophilic sudan IV remained for more than 10 days whereas tetracycline remained for 1 day in the pouch. The compatibility of the gels was also examined by histopathology. The gels did not cause any adverse inflammatory effect in the air pouch.KeywordsInjectable gel, Sustained release, Egg phosphatidylcholine, Hyaluronate